Website Provision of Accessibility Information By New Zealand Luxury Lodges: A Luxury for People With Disabilities? - Gillovic, Brielle; Harkison, Tracy-Lesley (CAUTHE, 2023)
Luxury tourism is a trillion-dollar sector that is only expected to grow, yet it has largely been remiss in its consideration of people with disabilities. While the tourism and hospitality sectors have largely overlooked people with disabilities, it is well-documented that they represent a valuable market. Research has highlighted the many barriers to travel participation that this market face, including the lack of accurate, up-to-date and relevant information as critical. This working paper examines the websites of eight New Zealand Luxury Lodges and their provision of accessibility information. A major finding of this study is that minimal if any concern is given to the explicit provision of information regarding the accessibility of the rooms or wider premises, unless solicited through direct contact. It could be inferred then that luxury accommodation providers are not meeting the information needs of potential guests, and thus missing out on the business of this growing market.
Keywords: accessible tourism; luxury accommodation; New Zealand; people with disabilities; information needs; website content analysis